Development and implementation of remote steering - Bergström, Ossian; Wernersson, Tobias (My University, 2021)
During the last couple of years, the strive for developing autonomous cars has drastically increased. With this said, new problems arise parallel to the evolution of this new technology, as it grows bigger. This thesis examines an alternative way of steering these autonomous cars, when the cars themselves malfunction or are unable to manage a certain situation. Volvo Cars AB presented a thesis concept that involves an investigation of the possibilities of steering a Volvo XC60 remotely from a central communication unit. The method applied to achieve this utilized UDP data transmission over Wi-Fi and a remote gaming steering wheel. To remotely send the input steering angle value from the remote steering wheel to be received by a VN8911 module implemented on a test rig in the first phase of the thesis and later on being implemented on a XC60. To analyse if the implementations and the alternative way of steering the XC60 remotely, function as intended. A couple of qualitative oriented tests were performed to determine whether the alternative way of steering will work in practise. This based on the test drivers’ intuition and personal judgement. Furthermore, the test driver will manoeuvre the car simultaneously as watching a live streamed video of the test course with the help of a GoPro Hero 8. Due to this being a bachelor thesis, some limitations were applied to cut down any unnecessary time demanding steps, in order to have enough time to finish within the timespan of the thesis. The limitations of the thesis will include Wi-Fi only being implemented during the test rig tests and not during the tests performed with the implementations on the XC60. Instead, the tests will be performed over LAN and the Wi-Fi latency that would have been applied will instead be replaced by a simulated time delay implemented in the sending UDP programming script. Furthermore, the test driver will simulate the remote environment of steering the car from the backseat watching the livestreamed video. Towards the end, the tests performed on the test rig provided an outcome enabling an implementation of the developed hardware and software setup, on a Volvo XC60. By analysing the data achieved from the tests performed on the car, an outcome indicating great drivability and manoeuvrability was achieved. Whilst operating during relatively high velocities and with different time-delays.
Keywords: Remote steering; UDP; CANoe; CAPL; VN8911; Python; Tests; Autonmous Cars